2022
DOI: 10.1101/2022.09.07.22279697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Journey Through Rural Community Radiography Practice in South-South Nigeria: Radiographers’ Perception, Willingness and Barriers

Abstract: Introduction: The lack of healthcare professionals and their retention in rural areas has become a serious concern to the health sector globally. Retaining health staff in rural areas has proven difficult as young professionals prefer urban postings. This study aimed to assess radiographers perception and willingness to work in rural areas of Rivers State. Method: This cross-sectional questionnaire-based study was conducted among radiographers in Rivers State. The participants socio-demographic variables and t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Improvements in provision of supplies and preventive measures are urgently needed in the face of the current pandemic. This is supported by another study [5] that, most countries have facilitated the transmission and spread of the disease due to inadequate preventive and/or mitigating strategies and many countries failed to prevent the epidemic in the beginning by delaying preventive measures. The study in Sierra Leone [4] found related results that, HCWs are of the view that their healthcare facilities are not well prepared to adequately respond to COVID-19 break.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Improvements in provision of supplies and preventive measures are urgently needed in the face of the current pandemic. This is supported by another study [5] that, most countries have facilitated the transmission and spread of the disease due to inadequate preventive and/or mitigating strategies and many countries failed to prevent the epidemic in the beginning by delaying preventive measures. The study in Sierra Leone [4] found related results that, HCWs are of the view that their healthcare facilities are not well prepared to adequately respond to COVID-19 break.…”
Section: Discussionmentioning
confidence: 77%
“…Although delayed government response, inadequate infrastructures, and lack of biosafety and biosecurity awareness have also contributed to the transmission and spread of COVID-19 disease [24]. Other studies [5,6] further revealed that, the fear of healthcare workers towards COVID-19 pandemic is reinforced by inadequate work place safety and inadequate hospital infection prevention and control policy. Consequently, majority of the participants strongly agreed that there was high possibility of getting the infection in the hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation